Magnet-Retained Facial Prosthesis Combined with Maxillary Obturator - Mahnaz Hatami; Hamid Badrian; Siamak Samanipoor; Marcelo Coelho Goiato (Case Reports in Dentistry)
Prosthetic rehabilitation of the midfacial defects has always perplexed prosthodontists. These defects lead to functional and esthetic deficiencies. The purpose of this clinical case report was the presentation of the prosthetic rehabilitation of an extraoral-intraoral defect using two-piece prosthesis magnetically connected. This prosthesis has dramatically improved the patient’s speech, mastication, swallowing, and esthetic.